الطابع المستعجل في دعاوى الحيازة وتأثيره في تحديد المحكمة المختصة - أبو العيال, أيمن; الوتار, سميرة (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يقصد بالاختصاص صلاحية المحكمة للبت في الدعوى المعروضة عليها، أي معرفة الجهة القضائية والمحكمة المؤهلة للنظر في النزاعات على اختلافها، وقوانين الاختصاص هي تلك القوانين التي تحدد ولاية المحاكم المختلفة، وأثناء النظر في دعاوى الحيازة فإنه يثار إشكال حول المحكمة المختصة للنظر في دعاوى الحيازة، فهل يكون الاختصاص لمحكمة الموضوع أم قاضي الأمور المستعجلة. وفي بحثنا هذا وصلنا الى نتيجة مفادها أنه وفي ظل غياب النص الصريح في القانون السوري فإنه يكون لقاضي الأمور المستعجلة النظر في دعاوى وقف الأعمال الجديدة وبعض حالات دعاوى استرداد الحيازة وذلك لتحقق عنصر الاستعجال فيها، واختصاص قضاء الموضوع بالنظر في دعوى منع التعرض ولكن على وجه السرعة لضمان حقوق المتقاضين.Intended to jurisdiction court the authority to decide the case before it, i.e knowledge of the judicial body qualified to look at the conflicts in all their court, and the laws of jurisdiction are those laws that determine the state of the various courts, and during the consideration of possession claims it raised Confusion about what is the competent court to consider possession claims , it would be the jurisdiction of the Judge sitting in chambers to deal with matters of special urgency. In our research we came to the conclusion that in the absence of explicit text in Syrian law, It will be the judge of urgent matters to consider the cessation of new business cases and some cases of lawsuits to recover possession so as to achieve the element of urgency, And eliminate the jurisdiction of the subject to consider action for disturbance of possession, But quickly to ensure the rights of litigants.